2010
DOI: 10.1089/ast.2009.0433
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Decomposition of Carboxylated Molecules on Light-Exposed Martian Regolith and Its Relation to Methane Production on Mars

Abstract: We propose that the paucity of organic compounds in martian soil can be accounted for by efficient photocatalytic decomposition of carboxylated molecules due to the occurrence of the photo-Kolbe reaction at the surface of particulate iron(III) oxides that are abundant in the martian regolith. This photoreaction is initiated by the absorption of UVA light, and it readily occurs even at low temperature. The decarboxylation is observed for miscellaneous organic carboxylates, including the nonvolatile products of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 71 publications
3
79
1
Order By: Relevance
“…Laboratory studies have shown that the evolution of mellitic acid produces a radiotolerant organic compound identified as benzenehexacarboxylic acid-trianhydride (C 12 O 9 ) (Stalport et al, 2009). To study a possible photocatalytic interaction of phthalic acid with martian regolith (Shkrob et al, 2010), this acid was also exposed together with JSC Mars-1, a mineralogical analogue of martian soil that is composed of volcanic ashes collected in Hawaii and exhibits similarities to some bright areas of Mars (Allen et al, 1998).…”
Section: Test Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have shown that the evolution of mellitic acid produces a radiotolerant organic compound identified as benzenehexacarboxylic acid-trianhydride (C 12 O 9 ) (Stalport et al, 2009). To study a possible photocatalytic interaction of phthalic acid with martian regolith (Shkrob et al, 2010), this acid was also exposed together with JSC Mars-1, a mineralogical analogue of martian soil that is composed of volcanic ashes collected in Hawaii and exhibits similarities to some bright areas of Mars (Allen et al, 1998).…”
Section: Test Moleculesmentioning
confidence: 99%
“…Numerical models predict that the surface of Mars is exposed to an energetic UV flux in the 190-400 nm range (Kuhn and Atreya, 1979;Cockell et al, 2000;Patel et al, 2002). Laboratory experiments have been developed to mimic such radiation conditions and evaluate their impact on organic materials likely to be present at the martian surface (Stoker and Bullock, 1997;Gontareva, 2005;Ten Kate et al, 2005Shkrob et al, 2010). Those studies highlighted the degradation of most of the organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…T he space science community agrees on the need to explore the martian subsurface for evidence of intact organic molecules (Kminek and Bada, 2006;Shkrob et al, 2010). In fact, ESA's ExoMars mission aims to search for life or its remains by analyzing samples taken from a drill hole of at least 2 m in depth (http://www.esa.int/SPECIALS/ExoMars/ SEM10VLPQ5F_0.html ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, if the branching ratio, factor (3), is on the order < 7% instead of 20%, there is no disagreement between the model and observations. Recent work by Wadsworth and Cockell (2017), building on previous work by Shkrob et al (2010), has argued that UVactivation of perchlorates in martian dust (Quinn et al, 2013) could result in enhanced destruction of microorganisms. While it is unclear whether such a process would yield methane, or if the process would degrade the organic carbon compounds found in IDPs, it is an example of a potential secondary process that could reduce the branching ratio to methane of available organic carbon at the surface of Mars.…”
Section: Where Is the Missing Methane?mentioning
confidence: 99%